The Linguistic Interpretation for Language Union – Language Family - E.A. Balalykina (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper is dedicated to the problem of determination of the essence of language union and language family in modern linguistics, which is considered important, because these terms are often used as absolute synonyms. The research is relevant due to the need to distinguish the features of languages that are inherited during their functioning within either language union or language family when these languages are compared. The research has been carried out in order to present the historical background of the problem and to justify the need for differentiation of language facts that allow relating languages to particular language union or language family. In order to fulfill the goal of this work, descriptive, comparative, and historical methods have been used. A range of examples has been provided to prove that some languages, mainly Slavonic and Baltic languages, form a language family rather than a language union, because a whole number of features in their systems are the heritage of their common Indo-European past. Firstly, it is necessary to take into account changes having either common or different nature in the system of particular languages; secondly, one must have a precise idea of what features in the phonetic and morphological systems of compared languages allow to relate them to language union or language family; thirdly, it must be determined whether the changes in compared languages are regular or of any other type. On the basis of the obtained results, the following conclusions have been drawn: language union and language family are two different types of relations between modern languages; they allow identifying both degree of similarity of these languages and causes of differences between them. It is most important that one should distinguish and describe the specific features of two basic groups of languages forming language family or language union. The results obtained during the analysis are very important for linguistics to differentiate language family from language union.